Legal Analysis of a Company Merger - Cyntia Vebrina Simamora; Anggusti, Martono; Sidauruk, Jinner (Journal of Law, Politic and Humanities, 2025)
Companies play a crucial role in the economy, both in terms of business, social, and environmental aspects. In facing global competition, merger strategies are one way companies use to improve efficiency, competitiveness, and market share. However, mergers also bring significant legal impacts, particularly regarding changes in organizational structure, human resource management, and compliance with applicable regulations. This study aims to analyze the positive legal impacts of the merger carried out by PT Pelindo Regional 1, including its effects on the legal status and ownership of the company, asset transfer, employee rights, and the potential reduction in competition levels. This research uses a normative juridical method with a library research approach, examining relevant regulations such as Law No. 40 of 2007 on Limited Liability Companies and Government Regulation No. 101 of 2021 on Company Mergers. The study finds that while mergers have the potential to enhance company efficiency and competitiveness, this process must be carefully managed to avoid legal issues, especially concerning employee rights and competition supervision. Therefore, companies need to ensure compliance with existing regulations and conduct due diligence to mitigate potential legal risks.